Environment friendly, transparent nanofiber textiles consolidated with high efficiency PLEDs for wearable electronics - Park, Mira; Lee, Kyu Seung; Shim, Jaeho; Liu, Yanan; Lee, Chohye; Cho, Hyunjin; Kim, Myung Jong; Park, Soo-Jin; Yun, Yong Ju; Kim, Hak Yong; Son, Dong Ick (ELSEVIER SCIENCE BV, 2016)
Electrospinning used to fabricate eco-friendly, transparent, human hair-based nanofibers (NFs) using natural resources such as keratin (which is found in hair, wool, feather, nails, and horns). These NF-based textiles are very useful in making transparent, wearable electronics, as they possess unique optical properties in the visible light regions, such as transparency exceeding 85%. The resulting environmentally friendly, hair-based NFs were investigated through various methods. In order to study transparent property of optically transparent NFs for applying transparent wearable devices, we fabricated transparent flexible consolidated sandwich structures embedded in NF textiles with polymer light-emitting diodes (PLEDs). The devices exhibit the fabrication process and characterization of consolidated textiles and PLEDs by using various color emission type of polymer. Also, we investigated a comparison between PLEDs without textiles and consolidated PLEDs with textile. When used white, red, and yellow polymer in this consolidated textile/LEDs/textile structures, the performances of device was obtained from a spectrally white, red, and yellow color light with a maximum luminance of 2781, 2430, and 6305 cd/m(2) at 13, 11, and 10 V, respectively. The LED characteristics of the consolidated PLEDs with textile maintained similar device efficiencies of PLEDs without textiles. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: SOLAR-CELLS; POLYMER; FABRICATION; STABILITY; NETWORKS; PAPER